A systematic review of problematic video-game use in people with Autism Spectrum Disorders. (April 2021) - Craig, Francesco; Tenuta, Flaviana; De Giacomo, Andrea; Trabacca, Antonio; Costabile, Angela
Highlights: People with ASD seem to be an especially vulnerable subpopulation for PVG use. Problematic video-game use may be an important clinical consideration for ASD. Social difficulties in real seem to be reflected in the gaming situation. Both internal and external factors were significant predictors of PVG use in ASD. Future psychometric studies are needed to promote measures suitable. Abstract: Background: In recent years, an increasing number of studies documented potential links between gaming disorders (GD; including "digital-gaming" or "video-gaming") and Autism Spectrum Disorders (ASD). Therefore, the aim of this systematic review was to summarize current research about problematic video game (PVG) use in people with ASD and identify specific factors associated with problematic video gaming behavior. Method: We searched for articles indexed in PubMed, Scopus, Web of Science, and EBSCOhost electronic databases; using a combination of expressions including "autism spectrum disorder" OR "autism" OR "ASD" AND "video games" OR "gaming disorder" OR "Internet Gaming Disorder" OR "game addiction". Results: Twelve articles were included in this systematic review. The majority of them indicate that children, adolescents and adults with ASD may be at greater risk of PVG use than youths without ASD. Findings also suggested that several internal (sex, attention and oppositional behavior problems) and external factors (social aspects, access and time spent playing video, parental rules, and game genre) were significant predictors of problematic video game use in people with ASD. In addition, this review highlights the paucity of the literature on the consequences and individual effects of excessive video gaming in people with ASD. Conclusions: We discuss unanswered questions and future directions and provide recommendations for improving clinicians and parents' engagement in the prevention and management of problematic video game use in people with ASD.